INTEGRASI NILAI ISLAMI DALAM PENERAPAN KURIKULUM MERDEKA PADA PENGAJARAN IPA SAINS DI MADRASAH IBIDAIYYAH - Nasir, Muhammad Fikri Abdun (Al-Mubtadi: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Currently, education faces various challenges due to significant changing times. The use of technology has influenced education widely. Where Education has an important role in answering and preparing the current and future generations. The Independent Curriculum is here as a solution to this problem, namely to give the right to learn independently. The purpose of this study is to describe the concept and implementation of the independent curriculum in the Islamic religion subject cluster in learning at the Integrated Islamic Elementary School MI Al-Ishlah Jepara. The research method is a qualitative approach with a descriptive research type. The research subjects were school principals and a team of teachers from the Islamic Religious Education family who developed the curriculum. Data collection is done by observation, interviews, and documentation. The data analysis technique was carried out using descriptive analysis, namely data presentation and conclusion. While testing the validity of the data is done with the Validity Test. The results of the research show that the Merdeka Curriculum was born as a curriculum capable of developing innovation in creating a fun learning atmosphere and in line with national education goals. Implementation. Merdeka Curriculum at the MI level to strengthen the Pancasila Student Profile. The concept of the Independent Curriculum encourages students to be active, creative, and think independently in developing their knowledge and skills. The implementation of the independent curriculum in Integrated Islamic Elementary Schools which is characterized by the character of Islamic learning uses the Independent Sharing Category, namely the school implements the Independent Curriculum at the first and fourth grade levels of MI and develops its own teaching tools, especially in Islamic subject groups.